Wissenserwerb im Kontext schulgeographischer Exkursionen: Potenzial und Grenzen kognitivistischer und konstruktivistischer Exkursionen - Neeb, Kerstin (Zeitschrift für Geographiedidaktik (ZGD), 2011)
The acquisition of competence in the area of knowledge constitutes an essential feature to assess the output of learning by excursions in the context of geographical education in school. Different, cognitivist and constructivist designs of excursions may expect specific possibilities of acquiring competence in the area of knowledge. So far, this aspect has not been explored empirically in the academic community. In the context of this research the main effort is focused on answering questions to demonstrate the potential and especially the limits of a cognitivist and a constructivist excursion with regard to the acquisition of competence in the area of knowledge by offering an empirical foundation. The results of the empirical survey built the basis to demonstrate specific characteristics of different excursions, to determine first trends to assess a cognitivist and constructivist didactic of excursions and to show up possibilities and future aspects for further research in the context of the didactic of excursions.